Calf morbidity and mortality rates Associated risk factors in smallholder dairy farms in Kembata Tembaro zone, Southern Ethiopia - Yohannes, Teshome; Geinoro, Tariku (Ovozoa: Journal of Animal Reproduction, 2024)
A study was carried out in the Kembata Tembaro Zone of Southern Ethiopia, focusing on both prospective cohort and cross-sectional surveys. The objective was to measure the rates of calf sickness and death and to pinpoint the factors that contribute to these conditions. Over 180 days, 140 newborn calves from selected small-scale dairy farms were studied. The study evaluated the prevalence of illness, mortality, and specific diseases by calculating incidence rates. Results indicated a 41.7% risk of illness and a 9.5% mortality rate among calves. Factors such as the calf's condition at birth, birth location/environment, the surface on which the calf was born, timing of the first colostrum intake, maternal parity, calf breed, and the breeding service technique significantly influenced mortality rates. Similarly, these factors were also significantly linked to the crude morbidity rate. Calves born naturally were at a lower risk of sickness (HR=0.6, p=0.001) compared to those assisted. Calves born indoors had a lower risk of sickness (HR=0.9, p=0.008) than those born outdoors. Calves that received colostrum within six hours of birth had a lower risk of sickness (HR=0.6, p=0.009) than those that received it later. Additionally, the study found that the floor of the birth place, the mother's parity, the breed of the calf, and the technique of the breeding service were additional risk factors for calf sickness. The time of the first colostrum intake, the mother's parity, and the calf's birth condition were also significant risk factors for calf death.